MPI-EVA – PUCP interdisciplinary research program on Amazonian linguistic diversity (third phase) - (:unkn) unknown (My University, 2026)
The project intends -this year- to continue and expand the collaborative research program on South American linguistic diversity, jointly developed by the Department of Linguistic and Cultural Evolution (DLCE) at the Max Planck Institute for Evolutionary